Five new species of the Simulium decuplum subgroup of the Simulium (Gomphostilbia) batoense species-group (Diptera: Simuliidae) from Thailand and their phylogenetic relationships - Hiroyuki Takaoka (2018)
© 2018 Elsevier B.V. Five new species of black flies, Simulium (Gomphostilbia) chiangraiense, S. (G.) huaikaeoense, S. (G.) khaokhoense, S. (G.) maeklangense, and S. (G.) pamiangense, are described based on adults, pupae and mature larvae from Thailand. These five species are similar to one another and are placed in the S. decuplum subgroup of the S. batoense species-group by having the male fore coxae darkened, ventral plate flat and transverse; pupal gill with 10 short filaments; and larval postgenal cleft deep approaching or reaching the posterior margin of the hypostoma. Simulium (G.) chiangraiense sp. nov. and S. (G.) pamiangense sp. nov. differ from the three other new species by the much longer pupal gill filaments and darkened dorsal surface of abdominal segments 1 and 2. Taxonomic notes are provided to distinguish these five new species from five other related species. The phylogenetic positions of these new species in the S. decuplum subgroup are presented based on the mitochondrial COI gene. Simulium (G.) pamiangense sp. nov. and S. (G.) huaikaeoense sp. nov. are highly similar to each other genetically, showing a sister relationship, though they are clearly different morphologically. On the contrary, S. (G.) khaokhoense sp. nov. is distantly positioned from S. (G.) huaikaeoense nov., though it is almost indistinguishable morphologically from the latter.